2022
DOI: 10.3390/nu14173467
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis after Traumatic Brain Injury Contributes to Persistent Microglial Activation Associated with Upregulated Lyz2 and Shifted Tryptophan Metabolic Phenotype

Abstract: Traumatic brain injury (TBI) is a common cause of disability and mortality, affecting millions of people every year. The neuroinflammation and immune response post-TBI initially have neuroprotective and reparative effects, but prolonged neuroinflammation leads to secondary injury and increases the risk of chronic neurodegenerative diseases. Persistent microglial activation plays a critical role in chronic neuroinflammation post-TBI. Given the bidirectional communication along the brain–gut axis, it is plausibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…An early increase in A. muciniphila may be part of a compensatory response to systemic damage initiated by TBI. Recently, A. muciniphila levels were shown to be reduced at 1 wk and 4 wk in mice receiving CCI of a similar severity to the present study 82 , suggesting that trauma-induced changes in A. muciniphila may be biphasic.…”
Section: Discussionsupporting
confidence: 86%
“…An early increase in A. muciniphila may be part of a compensatory response to systemic damage initiated by TBI. Recently, A. muciniphila levels were shown to be reduced at 1 wk and 4 wk in mice receiving CCI of a similar severity to the present study 82 , suggesting that trauma-induced changes in A. muciniphila may be biphasic.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, it was reported that the abundance of Patescibacteria , Saccharimonadales , and Saccharimonadia was increased in patients with Alzheimer’s disease and mild cognitive impairment ( Zhu et al., 2022 ), and Patescibacteria was enriched in mice with neurobehavioral impairments ( Diao et al., 2021 ). Furthermore, Rikenellaceae was the main dominant bacteria in mice after 28 days of TBI injury ( Zheng et al., 2022 ), and the abundance of Alistipes increased in patients with chronic TBI ( Urban et al., 2020 ). Moreover, the levels of Rikenellaceae and Alistipes were increased in rats with anxietylike behavior, accompanied by the activation of neuroinflammatory microglia and the increase of IL-1β expression in the hippocampus ( Wu L. et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Urban RJ et al [ 58 ] reported significant reductions in tryptophan metabolites in TBI patients even years later. Our team [ 66 ] noted altered intestinal metabolism in mice post-TBI and particularly marked changes in tryptophan metabolism at 7 and 28 days post-injury. Specifically, the indole pathway of tryptophan metabolism demonstrated shifts at 7 days post-injury, returning to baseline at 28 days.…”
Section: Changes In Tryptophan Metabolites and Ahr After Tbimentioning
confidence: 99%
“…Zheng et al [ 70 ] observed, in a rabbit TBI model, increased mRNA expression of vital enzymes in the tryptophan-kynurenine pathway, highlighted by significant upregulation of IDO1 mRNA expression in the TBI group at all time points post-injury ( p < 0.05). Our own investigation [ 66 ] unveiled that at 7 days post-TBI, kynurenine significantly rose and KYNA decreased, but by 28 days post-TBI, kynurenine remained unchanged, KYNA increased, and both xanthinic acid (XA) and 8-methoxy-kynurenic acid consistently decreased. The first human evidence of post-TBI abnormalities in KP was from QuinA analysis in the cerebrospinal fluid (CSF) of patients with severe TBI, showing a substantial increase around 72–83 h post-injury [ 71 ].…”
Section: Canine Uric Acid Pathwaymentioning
confidence: 99%